Efficacy of different techniques in attenuation of the pain caused by intravenous propofol injection: Efficacy of different techniques in attenuation of the pain caused by intravenous propofol injection - Syed Zaidan Shuja; Muhammad Fahad Farooq; Jawad Hameed; Atekah Alam; Amjad Nadeem; Afnan Raza (Medical Journal of South Punjab, 2024)
Objective: to compare the effectiveness of various drugs in attenuation of intravenous propofol injection pain. Methodology: Study was conducted at the department of anesthesia Lady Reading Hospital Peshawar, Pakistan from March 2023 to February 2024. Patients were assigned randomly to one of three groups using sealed envelopes. Each group consisted of 25 individuals. Drug solutions were prepared by a co-supervisor and dispensed in 5 ml doses by an observer. Group A received intravenous magnesium sulfate, Group B received intravenous granisetron, Group C received intravenous nitroglycerine. Results: Pain score 0 grade at 5 seconds in Group A, B and C was 36.0%, 40.0% and 44.0%, respectively. [?2=1.71, p=0.789]. Pain score 0 at 10 seconds in Group A, B and C was 32.0%, 76.0% and 32.0%, respectively. [?2=12.64, p=0.002]. Pain score 0 at 15 second in Group A, B and C was 40.0%, 60.0% and 36.0%, respectively. [?2=3.34, p=0.198]. Whereas, pain score 0 at 20 second in Group A, B and C was 4 (16.0%), 44.0% and 24.0%, respectively. [?2=5.16, p=0.076]. Conclusion: The present study suggests that pain experienced during intravenous injection of propofol can be reduced by using various medications. Among these medications, most effective drug was granisetron, followed by nitroglycerin and magnesium sulfate, with no significant complications in postoperative time.